PRODUCTION OF POTENT NEUTRALIZING POLYCLONAL ANTIBODIES AGAINST SEVERE ACUTE RESPIRATORY SYNDROME-CORONAVIRUS-2 (SARS-CoV-2) IN RABBITS, IMMUNIZED WITH RECEPTOR BINDING DOMAIN HEPATITIS B SURFACE ANTIGEN CONJUGATE PROTEIN AND WHOLE INACTIVATED SARS-CoV-2 (MT416726): A COMPARATIVE STUDY - YADAV, DHAIRYASHEEL; KADAM, NANDKUMAR; KARUPPAYIL, S. MOHAN; VIKHARANKAR, MAYUR; SHALIGRAM, UMESH; JADHAV, ASHWINI K. (International Journal of Applied Pharmaceutics, 2025)
Objective: The current study aims to produce potent neutralizing polyclonal antibodies against novel Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) by immunization of rabbits. Methods: Whole inactivated SARS-CoV-2 and purified Receptor Binding Domain-Hepatitis B surface Antigen (RBD-HBsAg) conjugate protein were used as immunogens along with Freud’s incomplete adjuvant for systematic immunization in rabbits by following a protocol approved by the Committee for Control and Supervision of Experiments on Animals (CCSEA) approved Institutional Ethics Committee (IAEC). During the systematic immunization cycle, blood samples were collected periodically after some intervals and checked for in vitro efficacy against SARS-CoV-2 by using Enzyme-Linked Immunosorbent Assay (ELISA) and Plaque Reduction Neutralization Test (PRNT50) methods. Results: The study revealed that 28, 35, and 42 d are required to generate high-neutralizing hyperimmune polyclonal antibodies in rabbits against immunogens. A combination of Freud’s incomplete adjuvant with whole inactivated SARS-CoV-2 and RBD-HBsAg conjugate protein has shown good response in the generation of potent highly specific polyclonal antibodies. RBD-HBsAg Conjugate protein has shown threefold more immunogenicity and neutralizing efficacy as compared to a whole inactivated SARS-CoV-2. Conclusion: Rabbits immunized with RBD-HBsAg Conjugate protein immunogen generated high neutralizing and more specific polyclonal antibodies. After extensive preclinical and clinical studies, such purified polyclonal antibodies can be used as alternative therapeutic drugs against SARS-CoV-2 infection.